PENGELOLAAN BANDAR UDARA TEMPULING KABUPATEN INDRAGIRI HILIR TAHUN 2011-2014 - Asfaringga, Ricky; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study tried to find out how the airport management Tempuling Indragiri Hilir Year 2011-2014 and the factors that cause a vacuum in the regular flights airport Tempuling Indragiri Hilir Year 2011-2014. The research is a qualitative research method of data collection deskriptif. Research using observation, interviews and documentation by using key informants as a source of information about the study.Data obtained from the result of management of airports Tempuling Indragiri Hilir year 2011-2014 consists of planning, implementation, monitoring and policy. Planning, Implemation, monitoring and policy, the private sector does not want to invest, not timely deparatures and arrivals, lack of supervision of the regional representatives council Indragiri Hilir, airport where motor racing.Factors that cause vacuums regular flights at airports Tempuling Indragiri Hilir Year 2011-2014. Cause by several factors that affect human resources, facilities and infrastructure is not yet complete, the lack of coordination with the relevant agencies and airlines suffered losses.Keyword : Airport Management, Planning, Implementation, Controlling, Police